Grey Relational Analysis For Piping Systems Subject To Corrosion Under Insulation - Ahamad Azahari, Ahmad Syahmi (Universiti Teknologi PETRONAS, 2017)
CUI problem is a very serious issue mainly in processing plant which have recorded many worst effects especially to the economy and production efficiency. Proactive measures must be done to control the issue as the piping insulation is used in many important sectors. Previously, a few methods of inspection to avoid the effects of CUI have been done. However, they are not quite efficient as need high cost and quite time consuming. In this research, a model of Grey Relational Analysis (GRA) have been developed to analyze the uncertain pipe corrosion data collected from the plant to obtained pipe ranking from the pipe with highest score to the lowest. A ranking of corrosion rate based on API standard also developed for comparison process. The parameters that have been considered for ranking are marine driver corrosion rate which determined based on operating temperature, pipe insulation types and pipe diameter. The results of ranking obtained are validated through comparison evaluation with actual ranking of pipes corrosion rate from the plant. The final ranking can be used for inspection prioritization.